1990
DOI: 10.1111/j.1365-2923.1990.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic, social and cultural factors influencing medical school grade performance

Abstract: Studies of medical student performance have focused on various factors, including premedical academics, maturity, familial background and support, and personal experiences with illness. Most studies have been conducted in countries with highly developed educational systems and similar cultural and social systems. It is not clear that these findings can be applied to developing countries, where the educational and cultural experiences may be very different, and where medical instruction is carried out in a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
3
29
0
Order By: Relevance
“…Finally, it is of note that whilst taking deferred entry appeared to be a negative predictor of success for the whole 21 years (Table 5), this was not the case for the more recent 5‐year cohort. Speculatively, this might be because taking a gap year is now much more commonplace and thus is less likely to reflect uncertainty about whether medicine is the correct career choice.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, it is of note that whilst taking deferred entry appeared to be a negative predictor of success for the whole 21 years (Table 5), this was not the case for the more recent 5‐year cohort. Speculatively, this might be because taking a gap year is now much more commonplace and thus is less likely to reflect uncertainty about whether medicine is the correct career choice.…”
Section: Discussionmentioning
confidence: 89%
“…This study shows no extremes in scores in any of the personality factors and minor variations in personality could influence academic performance. However, these findings may be confounded by other factors influencing academic performance such as premedical achievement, competence in English, mode of learning and family or social factors (Alfayez et al 1990; Biggs et al 1991; Parker 1993). It would be useful to address such issues in relation to students' academic performance in future.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies investigated factors that may affect academic performance during students' progress in medical schools. These studies have shown that the factors influencing students' GPA may include students' proficiency in English, student's self motivation, applying time managing skills, learning style, type of study references, study skills and socioeconomic status of students (Ahmed et al 1988;AlFayez et al 1990;Sansgiry et al 2006;Sleight & Mavis 2006;Wen-Bin 2008;Gurpinar et al 2010;Amrai et al 2011). Betts & Morell (1999) investigated different factors which may affect the undergraduate GPA.…”
Section: Introductionmentioning
confidence: 98%